2005
DOI: 10.1111/j.1572-0241.2005.40028.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Violet Chromoendoscopy with Mucosal Pit Pattern Diagnosis is Useful for Surveillance of Short-Segment Barrett's Esophagus

Abstract: The combination of crystal violet chromoendoscopy and pit pattern diagnosis is considered to be useful for the surveillance of short-segment Barrett's esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 32 publications
1
44
0
2
Order By: Relevance
“…† † † † H. pylori infection appears to be protective for AC H. pylori infection appears to be protective for AC H. pylori (17,19), while a risk factor for OSCC. It has been suggested that the rising incidence of OC seen in western countries may in part be explained by the increasing treatment and eradication of H. pylori infection (31) oesophagus (38). Light-induced fl uorescence endoscopy (LIFE) and narrow band imaging (NBI) are two additional endoscopic techniques for improving sensitivity in fi nding early lesions.…”
Section: Clinical Presentation/ Diagnosismentioning
confidence: 99%
“…† † † † H. pylori infection appears to be protective for AC H. pylori infection appears to be protective for AC H. pylori (17,19), while a risk factor for OSCC. It has been suggested that the rising incidence of OC seen in western countries may in part be explained by the increasing treatment and eradication of H. pylori infection (31) oesophagus (38). Light-induced fl uorescence endoscopy (LIFE) and narrow band imaging (NBI) are two additional endoscopic techniques for improving sensitivity in fi nding early lesions.…”
Section: Clinical Presentation/ Diagnosismentioning
confidence: 99%
“…We have been conducting Barrett's surveillance with crystal violet chromoendoscopy [2,14] for 2 years. In the first year, six Barrett's cancers and 15 dysplasias were found in 1963 consecutive esophagogastroduodenoscopies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the depth of tumor invasion ranked as m-3 but also indicated blood vessel involvement. We investigated the relationship between tumor depth and vessel involvement in early-stage Barrett's cancer as recorded in the literature [2,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). Fifty-six cases with mucosal Barrett's cancer and 53 with submucosal cancer [male : female = 87 : 22; median age, 62.3 years (range, 54-88 years)] were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic surveillance for BE may already be required in some Asian countries, including Japan, and some investigators have reported surveying methods for SSBE with special endoscopic techniques such as chromoendoscopy or image-enhanced endoscopy. [12][13][14][15] A reliable diagnosis of BE depends on the accurate endoscopic recognition of the key anatomic landmarks for the esophagogastric junction (EGJ) and squamocolumnar junction (SCJ). The precise localization of the EGJ is much more difficult than the endoscopic identification of the SCJ.…”
Section: Introductionmentioning
confidence: 99%